The AN EXAMINATION OF THE CHEFS’ PERSPECTIVES ON CONVENIENCE FOODS - Gaurav Khurana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
When and how much to employ ready-to-eat meals is a constant debate in the hospitality sector. There has never been an explicit examination of this subject in the hospitality literature, despite its relevance. Paper and pencil surveys were then administered to university food managers in an effort to better understand this issue. Convenience food items save time and money, but their perceived consistency and greater portion control aren't as essential to consumers, according to the results of the study. Non-convenience meals also tend to improve client connections, appealing to certain demographics, and the aesthetic attractiveness of finished products